Akurasi Mid Upper Arm Circumference (MUAC) dalam Mendeteksi Malnutrisi Akut pada Anak di bawah 5 Tahun : A Literature Review: Tinjauan Literatur : Akurasi MUAC dalam Mendeteksi Malnutrisi Akut - Ariza, Nahya Rahmatul; Siti Rahayu; Willmart, Auresa Caesarputriaulya (Universitas Airlangga, 2023)
Background: Fast and accurate detection of acute malnutrition is important to prevent death. The use of Mid Upper Arm Circumference (MUAC) can be an alternative but its accuracy is still being explored because many differences in research results are found. Objectives: This literature aimed to identify the accuracy (sensitivity and specificity) and optimal MUAC cut-off in detecting acute malnutrition in children under 5 years. Methods: Search for articles using Google Scholar and Pubmed with the keywords